Synthesis of monoclinic and cubic (metastable) nanocrystalline HfO2 through the nitrate fusion technique. Issue 15 (15th October 2017) - Kumar, D. Sanjay; Ananthasivan, K.; Venkata Krishnan, R.; Amirthapandian, S.; Ravindran, T.R.; Balakrishnan, S.
Abstract: For the first time it was demonstrated that nanocrystalline hafnia powders i.e. both the thermodynamically stable monoclinic phase and the metastable cubic phase could be synthesized by tailoring the nitrite to nitrate mole ratio (Φ) of the eutectic mixtures containing KNO3, NaNO3 and NaNO2 . All these nanocrystalline HfO2 powders were characterized for their bulk density, size distribution of particles, specific surface area, carbon residue and X-ray crystallite size. All powders exhibited unimodal size distribution of particles. Transmission electron microscopy and Raman spectroscopy reaffirmed the values of crystallite size estimated through XRD investigations and the identity of the constituent phases. Grain coarsening was observed when the powders were heat treated at 1473 K. Highlights: Fine grained nanocrystalline hafnia was synthesized for the first time in bulk by using nitrate fusion technique. It was shown that by tailoring the melt composition metastable cubic hafnia could be obtained. The metastable c-HfO2 phase transforms into the stable m-HfO2 phase at 1073 K . Raman studies confirmed that the mixtures with the Φ values 0–0.32 and 0.82 yielded m-HfO2 and c-HfO2 respectively. Minimum annealing temperature necessary to bring about significant grain growth was found to be 1473 K.